2022
DOI: 10.3390/su14074297
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Farmers’ Attitudes towards Rural Land Circulation Policy Changes in the Pearl River Delta, China

Abstract: An emerging and pressing issue in China’s economic reform is the intensified conflict between arable land protection and the encroachment of urban development into fertile farmlands that threaten food security and urban sustainability. New policies were issued to encourage rural land circulation as an attempt to ensure urban development and a sustainable food system, but farmers’ willingness to adopt the policies is largely unknown. A total of 4500 farmers within 9 cities’ boundaries in the Pearl River Delta w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…5 . The comprehensive characteristics including economically developed areas, large topographic differences between east and west, and the continuous spread of farmland abandonment reflect the changes in people’s attitude towards farmland in the process of China’s rapid economic development (Li et al 2022c ; Xie et al 2017 ), and it is also an ideal place to study the mechanism of farmland abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…5 . The comprehensive characteristics including economically developed areas, large topographic differences between east and west, and the continuous spread of farmland abandonment reflect the changes in people’s attitude towards farmland in the process of China’s rapid economic development (Li et al 2022c ; Xie et al 2017 ), and it is also an ideal place to study the mechanism of farmland abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…5. The comprehensive characteristics including economically developed areas, large topographic differences between east and west, and the continuous spread of farmland abandonment reflect the changes in people's attitude towards farmland in the process of China's rapid economic development (Li et al, 2022b;Xie et al, 2017), and it is also an ideal place to study the mechanism of farmland abandonment. study area from 2010 to 2018 There were differences in the impact of different variables on farmland abandonment in the study area.…”
Section: Influence Mechanism Of Farmland Abandonment In Developed Countymentioning
confidence: 99%
“…Yang [28] investigated the influence of land fragmentation on farmers' crop rotation behavior. Li [29] found that farmers' awareness of policies positively influences their willingness to participate in land transfers. Niu [30] suggests that factors such as gender, education level, labor force size, land area, migration from traditional agricultural areas, average family income, and understanding of policies significantly affect farmers' behavior.…”
Section: Introductionmentioning
confidence: 99%